(untitled) (Journal of the College of Basic Education, 2022)
The 2-[(2,4-dinitro-phenyl)-hydrozono methyl]-phenol was prepared by the reaction of salicylaldehyde with 2,4-dinitrophenylhydrazine, the prepared ligand was identified by Microelemental Analysis, FT.IR and UV-Vis spectroscopic techniques. Treatment of the prepared ligand with the following selected metal ions (NdIII,GdIII,DyIII and ErIII) in aqueous ethanol with a 1:3 M:L ratio, yielded a series of complexes of the general formula [M(L)3]. The prepared complexes were characterized by using flame atomic absorption, (C.H.N) Analysis, FT.IR and UV-Vis spectroscopic methods as well as conductivity measurements. From the obtained data the octahedral structure was suggested for all prepared complexes.